An Environmental Assessment Framework for Energy System Analysis (EAFESA): The method and its application to the European energy system transformation. (10th January 2020) - Xu, Lei; Fuss, Maryegli; Poganietz, Witold-Roger; Jochem, Patrick; Schreiber, Steffi; Zoephel, Christoph; Brown, Nils
Abstract: Coupling life cycle assessment (LCA) and energy systems models (ESM) is a suitable approach to assess energy systems from both life cycle and energy systems perspectives. However, methodological challenges need to be taken into account due to differences between both modeling approaches considering system boundaries, databases, and different levels of detail of their input data. This paper brings these challenges into discussion and introduces the Environmental Assessment Framework for Energy System Analysis (EAFESA), which enables to identify life cycle based non-climate environmental impacts of energy scenarios consistently. EAFESA is applied to analyze potential future decarbonized European electricity systems with a focus on flexibility options using ELTRAMOD as an example of an ESM to test the conceptual approach of combining ESM and LCA. The application confirms the importance and benefits of "integrated thinking" proposed by EAFESA, which allows minimizing the pitfalls of combining both models comprehensively. At the same time, EAFESA has the potential to bring awareness of issues not discussed among policy-makers. One example is the insight that the decarbonized electricity system will be accompanied by increased metal demand and urban land occupation. Highlights: The challenges of coupling LCA and ESM are discussed. EAFESA is proposed as a general and holistic framework to overcome the challenges. EAEFSA is applied to assess the future EU28 + 2 electricity system with flexibility options. Policy implications beyond climate change are proposed in the application.